Initiation and maintenance of cardiovascular medications following cardiovascular risk assessment in a large primary care cohort: PREDICT CVD-16. (29th August 2020) - Mehta, Suneela; Wells, Sue; Grey, Corina; Riddell, Tania; Kerr, Andrew; Marshall, Roger; Ameratunga, Shanthi; Harrison, Jeff; Kenealy, Tim; Bramley, Dale; Chan, Wing Cheuk; Thornley, Simon; et al.
Abstract: Aim: To examine whether use of a standardized cardiovascular disease (CVD) risk assessment recommended by national guidelines is associated with appropriate initiation and maintenance of medication in a large primary care cohort. Methods and design: A total of 90, 631 people aged 30−80 years were followed for up to 3 years after a formal CVD risk assessment was undertaken between January 2006 and October 2009, during routine primary care visits in New Zealand. Patients either had prior CVD or had their CVD risk estimated using a modified Framingham prediction equation for fatal or non-fatal CVD events. The individual risk profiles were anonymously linked to national dispensing data for blood-pressure-lowering and lipid-lowering medications in the 6-month period before and in consecutive 6-month blocks after the baseline CVD risk assessment. Results: At baseline, a combination of blood-pressure-lowering and lipid-lowering therapy was already being used by about two-thirds of patients with prior CVD, one-quarter with a 5-year CVD risk greater than 10% (approximately 20% 10-year risk), and one-tenth with CVD risk below this level. Among these previously treated patients, dispensing rates for blood-pressure-lowering, lipid-lowering, or both medications together declined by only 4⊟16% up to 3 years after baseline assessment, irrespective of risk category. Among patients untreated at baseline, combination therapy was initiated within 6 months for 21% with prior CVD, 16% with 5-year CVD risk greater than 15% (approximately 30% 10-year risk and the national drug-treatment threshold), 10% with 5-year CVD risk between 10 and 14% (approximately 20⊟29% 10-year risk), and 3% in the lowest risk category. Across the study population, patients with prior CVD had the highest dispensing rates for each category of medication, and incrementally higher dispensing rates were noted as CVD risk group increased. Conclusions: In this primary care cohort, most patients already using CVD medications at the time of the baseline CVD risk assessment maintained treatment over a maximum of 3 years follow up, irrespective of their estimated baseline risk. Among patients untreated at baseline, subsequent dispensing rates were strongly related to estimated CVD risk group. Around 15⊟20% of untreated patients meeting national drug-treatment criteria commenced combination pharmacotherapy within 6 months of CVD risk assessment.